The Effect of Shuttle Run Training on the Results of Dribbling Agility in Football Athletes - Kurniawan, Yuka Firdaus; Yusfi, Herri; Bayu, Wahyu Indra (Journal Coaching Education Sports, 2023)
The low understanding of techniques in soccer games includes dribbling technique, which refers to ball control and maneuvering using the feet. The aim of this research is to determine the influence of Shuttle Run training on the agility of dribbling skills in soccer athletes. The research design employed is a quasi-experimental study. The population of the study consists of 30 athletes from Sumber Harta Musi Rawas Soccer Club, aged between 17 and 20 years. The sample for this study is comprised of all 30 athletes from Sumber Harta Musi Rawas Soccer Club. The data analysis technique used is the "t-test" to obtain the results, with a critical value of 1.70 derived from the T-distribution table with degrees of freedom (df) of 39. The conclusion drawn from the study is that Shuttle Run training has a significant impact on improving dribbling agility in soccer games for the athletes of Sumber Harta Musi Rawas Soccer Club. The research findings also indicate that Shuttle Run training is an effective method for enhancing agility.